Emergency responses to acrylonitrile maritime spills from the perspective of marine ecological protection - Wang, Xiaotong; Meng, Fanping (Frontiers in Marine Science, 2022)
The increases in chemical shipping volumes increase the risk of hazardous noxious substances (HNSs) spills at sea. As one of the most frequently transported HNSs, acrylonitrile (ACN) spill incidents occur from time to time. The spilled ACN will have a wide range of short-term and long-term impacts on the marine environment. To reasonably standardise and optimise the emergency response countermeasures for ACN spill and maintain marine ecological health, the marine ecological hazards and physico-chemical behaviours of ACN were summarised. Based on this, the emergency response countermeasures for ACN spill at sea were studied and summarised in five aspects: spill source control, rapid prediction, emergency monitoring, numerical simulation and impact assessment, and elimination of ACN. This review forms a set of systematic emergency response countermeasures for deployment in ACN maritime spill incidents.